Analisis Koherensi dan Kohesi Teks Deskripsi - Putra Maulana, I Putu Ari; Dhanawaty, Ni Made; Madia, I Made (Humanis; Vol 23 No 3 (2019), 2019)
This study was titled "Coherence and Cohesion Analysis on the Text of Description for Class X Students of Denpasar Public High School 5". The problems examined in this study are three, namely the element of coherence, the tools of lexical cohesion, and the tools of grammatical cohesion in the text description of class X students of SMA 5 Denpasar. Based on the formulation of the problem, this study aims to explain the relationship of meaning or coherence, and describe the tools of lexical and grammatical cohesion. The theory used is discourse theory, namely coherence proposed by Kridalaksana and cohesion proposed by Halliday and R. Hasan. Based on the analysis that has been done on the description text of class X students of Denpasar Public High School 5 found several things. First, in the description text of class X Denpasar Public High School 5 found an element of coherence including causal relations, means-results, reasons, background-conclusions, concessions, comparisons, paraphrases, amplicatives, time additives (simultaneous and successive ), non-time additives, identification, generic-specific, means-purpose, and like. Second, lexical cohesion tools found include repetition (repetition), equivalent words (synonyms), opposite words (antonyms), word sanding (collocation), and equivalence (equivalence). Third, the tools of grammatical cohesion found include reference (reference), concatenation (conjunction), lapse (elipsis).